Hearing "Quack" and Remembering A Duck: Evidence for Fluency Attribution in Young Children. Issue 2 (15th September 2016) - Geurten, Marie; Lloyd, Marianne; Willems, Sylvie
Abstract : Previous research has suggested that fluency does not influence memory decisions until ages 7–8. In two experiments ( n = 96 and n = 64, respectively), children, aged 4, 6, and 8 years (Experiments 1 and 2), and adults (Experiment 2) studied a list of pictures. Participants completed a recognition test during which each study item was preceded by a sound providing either a highly predictive or mildly predictive context in order to make some test items more conceptually fluent. Overall, highly predictive items were recognized at a higher rate than mildly predictive items demonstrating an earlier development of the fluency heuristic than previously observed. The study provides insight into how children develop metacognitive expectations and when they start to use them to guide their memory responses.